Spinal and supraspinal modulation of pain responses by hypnosis, suggestions, and distraction. Issue 4 (12th April 2021) - Houzé, Bérengère; Streff, Anouk; Piché, Mathieu; Rainville, Pierre
ABSTRACT: The mechanisms underlying pain modulation by hypnosis and the contribution of hypnotic induction to the efficacy of suggestions being still under debate, our study aimed, (1) to assess the effects of identical hypoalgesia suggestions given with and without hypnotic induction, (2) to compare hypnotic hypoalgesia to distraction hypoalgesia and (3) to evaluate whether hypnotic suggestions of increased and decreased pain share common psychophysiological mechanisms. To this end, pain ratings, nociceptive flexion reflex amplitude, autonomic responses and electroencephalographic activity were measured in response to noxious electrical stimulation of the sural nerve in 20 healthy participants, who were subjected to four conditions: suggestions of hypoalgesia delivered with and without hypnosis induction (i.e. hypnotic-hypoalgesia and suggested-hypoalgesia), distraction by a mental calculation task and hypnotic suggestions of hyperalgesia. As a result, pain ratings decreased in distraction, suggested-hypoalgesia and hypnotic-hypoalgesia, while it increased in hypnotic-hyperalgesia. Nociceptive flexion reflex amplitude and autonomic activity decreased during suggested-hypoalgesia and hypnotic-hypoalgesia but increased during distraction and hypnotic-hyperalgesia. Hypnosis did not enhance the effects of suggestions significantly in any measurement. No somatosensory-evoked potential was modulated by the four conditions according to strict statistical criteria. The absence of a significant difference between the hypnotic hypoalgesia and hyperalgesia conditions suggests that brain processes as evidenced by evoked potentials are not invariably related to pain modulation. Time-frequency analysis of electroencephalographic activity showed a significant differentiation between distraction and hypnotic hypoalgesia in the theta domain. These results highlight the diversity of neurophysiological processes underlying pain modulation through different psychological interventions.